CXCL13 as a Biomarker of Immune Activation During Early and Chronic HIV Infection - Mehraj, Vikram; Ramendra, Rayoun; Isnard, Stéphane; Dupuy, Franck P.; Lebouché, Bertrand; Costiniuk, Cecilia; Thomas, Réjean; Szabo, Jason; Baril, Jean-Guy; Trottier, Benoit; Coté, Pierre; LeBlanc, Roger; et al. (Frontiers in Immunology, 2019)
Background: CXCL13 is preferentially secreted by Follicular Helper T cells (TFH) to attract B cells to germinal centers. Plasma levels of CXCL13 have been reported to be elevated during chronic HIV-infection, however there is limited data on such elevation during early phases of infection and on the effect of ART. Moreover, the contribution of CXCL13 to disease progression and systemic immune activation have been partially defined. Herein, we assessed the relationship between plasma levels of CXCL13 and systemic immune activation. Methods: Study samples were collected in 114 people living with HIV (PLWH) who were in early (EHI) or chronic (CHI) HIV infection and 35 elite controllers (EC) compared to 17 uninfected controls (UC). A subgroup of 11 EHI who initiated ART and 14 who did not were followed prospectively. Plasma levels of CXCL13 were correlated with CD4 T cell count, CD4/CD8 ratio, plasma viral load (VL), markers of microbial translocation (LPS, sCD14, and (1-->3)-B-D-Glucan), markers of B cell activation (total IgG, IgM, IgA, and IgG1-4), and inflammatory/activation markers like IL-6, IL-8, IL-1, TNF-, IDO-1 activity, and frequency of CD38+HLA-DR+ T cells on CD4+ and CD8+ T cells. Results: Plasma levels of CXCL13 were elevated in EHI (127.964.9 pg/mL) and CHI (229.428.5 pg/mL) compared to EC (71.320.11 pg/mL) and UC (33.414.9 pg/mL). Longitudinal analysis demonstrated that CXCL13 remains significantly elevated after 14 months without ART (p<0.001) and was reduced without normalization after 24 months on ART (p=0.002). Correlations were observed with VL, CD4 T cell count, CD4/CD8 ratio, LPS, sCD14, (1-->3)-B-D-Glucan, total IgG, TNF-, Kynurenine/Tryptophan ratio, and frequency of CD38+HLA-DR+ CD4 and CD8 T cells. In addition, CMV+ PLWH presented with higher levels of plasma CXCL13 than CMV- PLWH (p=0.005). Conclusion: Plasma CXCL13 levels increased with HIV disease progression. Early initiation of ART reduces plasma CXCL13 and B cell activation without normalization. CXCL13 represents a novel marker of systemic immune activation during early and chronic HIV infection and may be used to predict the development of non-AIDS events.